Pengaruh Penerapan Model Pembelajaran Translation, Analisys, Design, Implementation, Review (TADIR) Terhadap Hasil Belajar Peserta Didik Kelas VII Pada Materi Pencemaran Lingkungan Di SMPN 3 Kelara - Risna Amir; Muh. Rapi; Hamansah (Al-AHYA: Jurnal Pendidikan Biologi, 2022)
Important learning models are applied in a variety of ways in learning. One model that can be used is the Translation, Analysis, Design, Implementation, Review (TADIR) model. A quasi-experimental study with a non-equivalent control group design was chosen to determine the effect of the TADIR model on the learning outcomes of class VII students on environmental pollution at SMPN 3 Kelara. The research sample was selected by simple random sampling with class VII as the experimental class of 20 students and class VII B as the control class of 20 students. Data was collected through a test technique using multiple choice questions of 15 items. The research results were analyzed descriptively and inferentially using the t test. The results showed that the experimental class with the application of the TADIR model obtained an average posttest learning result of 74.5 higher than the control class with an average of 63.2. The significance value of the t-test was 0.000 <0.05, so it was concluded that the application of the Translation, Analysis, Design, Implementation Review (TADIR) learning model had an effect on the learning outcomes of class VII students on Environmental Pollution at SMPN 3 Kelara.